A controlled clinical trial of preoperative pain neuroscience education for patients about to undergo total knee arthroplasty. (November 2019) - Louw, Adriaan; Puentedura, Emilio J; Reed, Jordan; Zimney, Kory; Grimm, Derek; Landers, Merrill R
Objective: The aim of this study was to determine if a preoperative pain neuroscience education program would result in superior outcomes compared to usual preoperative education for total knee arthroplasty. Design: Controlled clinical trial with alternating allocation. Setting: Community-based hospital. Subjects: Consecutive sample of 120 patients scheduled for total knee arthroplasty. Intervention: Traditional hospital preoperative total knee arthroplasty education program on its own, or with an additional 30-minute group pain neuroscience education session. Main measures: Primary outcomes were measurements at one, three, and six months for pain, function, fear of movement, and pain catastrophization. We also compared opioid usage, healthcare expenses, and patient satisfaction between groups. Results: There were no statistically significant differences in any outcome measures between the two groups over time, except for patient satisfaction. Those in the experimental group had more agreement with statements about "preparation for surgery" ( P  = .038), "would do again" ( P  = .032), and "met expectations" ( P  = .033) compared to those in the control group averaged over the three measurement times. Patients improved in several outcome measures over time regardless of group assignment, with a 34% improvement in pain, 36% improvement in function, 16% improvement in fear of movement, and 23% improvement in pain catastrophization scores. Conclusion: Adding a brief 30-minute pain neuroscience education session to a traditional preoperative total knee arthroplasty education program did not result in any significant improvements, except patient satisfaction.